2010
DOI: 10.1111/j.1601-5037.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning climate in dental hygiene education: a longitudinal case study of a Japanese and Canadian programme

Abstract: Educational climates have been found to have important influences on learning, but little feedback has been obtained from dental hygiene students. The purpose of the present study was to gain an understanding of the learning climate in Japanese and Canadian dental hygiene programmes for the purpose of making positive changes. A survey instrument with 10 dimensions relating to learning climate was adapted from business and dental models, and designated as the Dental Hygiene Student Learning Climate Survey (DHS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(57 reference statements)
2
3
0
2
Order By: Relevance
“…indicated that Japanese dental hygiene students’ motivation towards the profession was significantly lower than Canadian students. These authors concluded that most of the Japanese students enrolled in the dental hygiene programme immediately after high‐school graduation without any work experiences . The length of education of the dental hygiene programme in Japan was once 1 or 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…indicated that Japanese dental hygiene students’ motivation towards the profession was significantly lower than Canadian students. These authors concluded that most of the Japanese students enrolled in the dental hygiene programme immediately after high‐school graduation without any work experiences . The length of education of the dental hygiene programme in Japan was once 1 or 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many instruments have been developed in the field of (graduate) medical educational that tap into learning climates [6], [28], [29]. In the Netherlands, the Dutch Residency Educational Climate Test (D-RECT) is the instrument used most to measure the learning climate within residency training programs as perceived by residents [23], [24].…”
Section: Methodsmentioning
confidence: 99%
“…(6). Öğrenme iklimi, öğrenme ortamının tonu ve atmosferi anlamına gelmektedir (7). Genn (2001)'e göre, müfredatın ve öğrenme ortamının 'ruhu ve canı' olarak tanımlanmaktadır (8).…”
Section: Introductionunclassified
“…Öğrenme ortamı algısının merkezinde öğrenme iklimi bulunmaktadır. İklim, başlı başına öğrenme ortamı ile ilgili değildir, öğrencilerin öğrenme ortamına nasıl yanıt verdiği yani öğrenme ortamı algısı ile ilgilidir (7). Öğrenme iklimi, öğrenmeyi etkileyen tüm değişkenleri kapsamaktadır ve öğrencilerin davranışlarını etkilediği, onlar tarafından algılanan öğrenme ortamının kalitesi ve bunun temel alındığı ortak davranışlar bütünü olarak tanımlanmaktadır (8).…”
Section: Introductionunclassified